Building a multi‐scale, collaborative, and time‐integrated digital crust: The next stage of the Macrostrat data system - Daven P. Quinn; Casey R. Idzikowski; Shanan E. Peters (Geoscience Data Journal, 2024)
Abstract Macrostrat is a platform for deep‐time geoscientific research that integrates stratigraphic columns and geologic maps into a digital description of the crust. The database and supporting software track crustal evolution and provide location‐based geological information to geoscience end users. Macrostrat houses multiple scales of mapping and stratigraphic data, from continent‐ and basin level summaries to single quadrangles and measured sections. Currently, Macrostrat's primary data holdings consist of regional stratigraphic columns with a spatial footprint weighted heavily to North America. While the data are of sufficient scale and resolution to generate insights about Earth evolution, increasing resolution and expanding spatial coverage will allow a new generation of scientific and interpretive uses. The next phase of Macrostrat's development will increase the detail and complexity of Macrostrat's multiscale data holdings, largely by engaging a wider range of geoscientists in entering stratigraphic data. To support broad collaboration, we are building new web‐based software to assemble and visualize regional stratigraphic sequences, refine multiple working age models, and compose regional records from measured stratigraphic sections. These tools will allow Macrostrat to draw on the expertise of a wide range of geoscience workers and grow a dataset with global relevance and a variety of end uses. New capabilities will pave the way to processes for submission, review, coordination, and assimilation of community‐contributed stratigraphic datasets. Digital compilation of geological maps and columns requires substantial effort, and well‐designed systems for distributing this work in the geoscience community will allow Macrostrat to build more adaptable and scientifically relevant products.